P3-S3.01 Anal Pap smear screening among drug users living with HIV in Miami, Florida. (10th July 2011) - Rosa-Cunha, I; Hooton, T; Cardenas, G; Metsch, L
Abstract : Background: Human papillomavirus (HPV) is associated with anal cancer. Human immunodeficiency virus (HIV) infection and cocaine use are associated with increased risk for HPV infection and associated diseases, but little is known about anal dysplasia among HIV-infected drug users. The objective of our study was to assess the rate of abnormal anal Pap smears among drug users living with HIV in Miami, Florida. Methods: Project HOPE (Hospital is an Opportunity for Prevention and Engagement) is a two-site study conducted in Miami and Atlanta to evaluate the efficacy of a brief prevention intervention for HIV-positive crack cocaine users recruited from two inner-city hospitals during their inpatient stays. At the Miami site, anal Pap smears from women and men (n=46) were collected. Results: The study population was 95% Black, the mean age was 47, 63% were female (29/46), 35% heterosexual males (16/46) and 2% men who have sex with men (MSM) (1/46). Approximately half of the participants did not complete high school, 50% were on antiretroviral therapy and 50% had been diagnosed with HIV for more than 14 years. The median CD4 cell count was 198. Overall 69.5% (32/46) of anal Pap smears were abnormal; 69% of women (20/29) and 70.5% of men (12/17) had abnormal Pap smear. Conclusions: These preliminary data suggest that abnormal anal Pap smears are common in drug users living with HIV in Miami and highlight the need for further studies on prevention and screening of anal dysplasia and cancer in this population.